ORGANIZATIONAL SUPPORT AND COLLABORATIVE CLIMATE AS PREDICTORS OF ORGANIZATIONAL CITIZENSHIP BEHAVIOR: THE MEDIATING ROLE OF AFFECTIVE COMMITMENT IN THE INDONESIAN PUBLIC SECTOR - Sulis Setiawan; Irsan Tricahyadinata; Sri Wahyuni (RADJA PUBLIKA, 2025)
In the current organizational landscape, organizational citizenship behavior (OCB) represents an essential driver of performance and innovation within the public sector. Employees’ willingness to perform beyond formal job duties often depends on how supported and valued they feel, as well as the degree of collaboration that characterizes their workplace. However, empirical evidence remains limited regarding how these contextual factors jointly enhance OCB through affective commitment, particularly in public institutions of developing regions. This study explores the mediating role of affective commitment in the relationship between perceived organizational support, collaborative climate, and OCB among civil servants in East Kalimantan, Indonesia. Using a quantitative explanatory approach and the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method with SmartPLS 4, data from 168 respondents were analyzed. The results indicate that supportive and collaborative work environments significantly strengthen OCB both directly and indirectly through affective commitment, emphasizing the importance of emotional attachment, empathy, and teamwork in fostering voluntary and constructive employee behavior.